The last kids on earth and the cosmic beyond - Brallier, Max; Holgate, Douglas (New York, New York : Scholastic, Inc., 2018)
"During the first winter after the Monster Apocalypse, Jack and his buddies prepare for a monstrous Christmas celebration, but a supervillainess steals Jack's prized monster-slaying weapon, his Louisville Slicer, and he vows to get it back." --
540L
Decoding demand: 91 (very high) Semantic demand: 100 (very high) Syntactic demand: 78 (high) Structure demand: 90 (very high)
Accelerated Reader AR
Keywords: Winter -- Juvenile fiction; Monsters -- Juvenile fiction; Supervillains -- Juvenile fiction; Weapons -- Juvenile fiction; Horror fiction; Comics (Graphic works); Graphic novels